Ngā tūpuna o Te Whanganui-a-Tara - Clarke, Sandra, 1941- (Wellington City Council, 2001)
Short biographies, including portraits where available, of Māori leaders of Port Nicholson (Te Whanganui-a-Tara) in the 1840s, written to give an overview of the hapū and iwi that had recently migrated from Taranaki during 1820-1840.